The Impact of the Global Financial Crisis and the Role of External and Internal Factors in Emerging Economies. Issue 2 (1st February 2017) - Dal Bianco, Silvia; Amini, Chiara; Signorelli, Marcello
ABSTRACT: This article assesses the impact of trade, capital openness and institutions on emerging economies' output loss during the "Great Recession." The fixed-effect estimates of an unbalanced panel of 122 emerging countries observed from 2008 to 2010 yield three main results. First, trade openness has exacerbated output loss. Second, capital openness can help mitigate the negative impact of an external shock, but this is conditional on the level of financial development. Finally, the results also point out that the interrelations between financial and institutional development affect the crisis's severity.